Calendar Art: An Overview - Dr. Mandakini Sharma; Shashikant Kakade; Richa Thapliyal, HSS (Elementary Education Online, 2023)
All Indian art forms that have a wide audience and rely on mechanical replication for both production and distribution are collectively referred to as "popular art" in the broadest sense. 1 The term "calendar art" refers to a kind of common print art. 2 more specifically, when thinking of calendar art, images such as colour prints made for framing to serve as wall decorations, artistically rendered illustrations that usually adorn hanging calendars, and polychrome lithographs that feature Gods and Goddesses and mysterious and captivating tales from their lives and times all come to mind. It was a mixture of popular and mythology when it was started. Suddenly, it captured a larger group of audience and almost everyone has it because of its variety and coverage of almost all themes and subjects. Even the calendar of every space is being designed with the advancement of modern applications. The digital calendar changed the perception of traditional ones and now almost every home, residence, and workstation has a calendar suitable for the surroundings. The study is a review of the art of Calendar from earlier to contemporary times.